Membrane adsorption or penetration differentially modulates β-galactosidase activity against soluble substrates - Sanchez, Julieta Maria (2002)
We investigated if in complex environments, like those where β-galactosidase activity is usually assayed, the kinetics of hydrolysis against soluble substrates could be modulated through enzyme-surface interactions. Kinetic parameters were determined using ortho-nitrophenyl-β-D-galactopiranoside (ONPG) as substrate, in the absence or presence of multilamellar vesicles (MLVs) of pure phosphatidyl cholines (PCs) or PCs:cholesterol mixtures, by visible spectroscopy. Light scattering was carefully corrected by three different methods obtaining similar results. The spectroscopic behavior of the reaction product in the presence of liposomes was also taken into account in order to avoid overestimating the reaction rate calculated from absorbance data. At low [PC] (<0.0024 mM) KM and Vmax decreased compared with the control in the absence of lipids. At high [PC] (1.2 mM), enzyme interaction with highly packed bilayers of dpPC induced an increment in both kinetic parameters. Both kinetic parameters decreased upon the interaction with low packed bilayers (soybean PC) at very low concentration (24 μM) but at higher concentration (1.2 mM) only an increment in Vmax was observed. The dpPC MLVs samples used were four times bigger than those of PCsoybean (approximately 1 μm mean diameter) as measured by quasi elastic light scattering. The increments in Vmax were due to a modulation of the kinetics of the enzymatic reaction and not to non-enzymatic hydrolysis of ONPG at the vesicle-water interface. Enzyme-membrane interaction was confirmed using monomolecular-layers at the air-water-interface. Interestingly, β-galactosidase showed a higher tendency to be localized at a lipid-water interface compared with the free air-water interface; membrane penetration was favored in lower packed membranes. Differences in surface curvature, and thus in surface molecular packing and hydration, might account for the effects observed as the main modulating factor. Our results suggest that β-galactosidase activity was differentially modulated according to the enzyme possibility to penetrate or just be adsorbed to a dimensionality restricted space. © 2002 Elsevier Science B.V. All rights reserved.